ΑB‐Crystallin R120G variant causes cardiac arrhythmias and alterations in the expression of Ca2+‐handling proteins and endoplasmic reticulum stress in mice. (August 2014) - Jiao, Qibin; Sanbe, Atsushi; Zhang, Xingwei; Liu, Jun‐Ping; Minamisawa, Susumu
Summary Mutations of αB‐crystallin (CryαB), a small heat shock protein abundantly expressed in cardiac and skeletal muscles, are known to cause desmin‐related myopathies. The CryαB R120G allele has been linked to a familial desminopathy and, in transgenic mice, causes a sudden death at about 28 weeks of age. To investigate the mechanisms of the sudden cardiac arrest of CryαB R120G transgenic mice, we prepared protein samples from left ventricular tissues of two different age groups (10 and 28 weeks) and examined Ca2+‐handling proteins. Expression of sarcoplasmic/endoplasmic reticulum calcium ATPase (SERCA) 2, phospholamban, ryanodine receptor 2 and calsequestrin 2 was significantly decreased in 28‐ versus 10‐week‐old CryαB R120G transgenic mice. In addition, low heart rate variability, including heart rate, total power and low frequency, was observed and continuous electrocardiogram monitoring revealed cardiac arrhythmias, such as ventricular tachycardia, atrioventricular block and atrial flutter, in 28‐week‐old CryαB R120G transgenic mice. In contrast, expression of endoplasmic reticulum (ER) degradation enhancing α‐mannosidase‐like protein, inositol requirement 1 and X‐box binding protein 1 were increased significantly in 28‐ versus 10‐week‐old CryαBR120G transgenic mice, suggesting that the CryαBR120G transgenic mice exhibit increased ER stress compared with wild‐type mice. Together, the data suggest that the CryαB R120G dominant variant induces ER stress and impairs Ca2+ regulation, leading to ageing‐related cardiac dysfunction, arrhythmias and decreased autonomic tone with shortened lifespan.